Polyazimuthal map projections Poliazimutne kartografske projekcije - Kerkovits, Krisztián (2020)
A polyazimuthal map projection is a mapping that represents parallels as non-concentric full circles on the plane. Polyazimuthal mappings are almost never mentioned in the literature dealing with map projections. However, these projections are flexible; their distortion characteristics are highly mutable. This paper expands the theory of polyazimuthal map projections. Furthermore, this study also shows the derivation for variants of this projection family (e. g. equal-area, orthogonal). The article concludes with some practical applications in the field of low-distortion map projections to demonstrate their advantages.
Poliazimutna kartografska projekcija je preslikavanje paralela kao nekoncentričnih kružnica u ravnini projekcije. Poliazimutna preslikavanja se ne spominju gotovo nigdje u literaturi o kartografskim projekcijama. Međutim, te su projekcije fleksibilne, a njihove distorzije jako promjenljive. Ovaj članak proširuje teoriju poliazimutnih projekcija. Nadalje, ova studija također daje izvod različitih varijanti takvih projekcija (npr. ekvivalentne, ortogonalne). Članak završava s nekoliko praktičnih primjena u području kartografskih projekcija s malim distorzijama kako bi se demonstrirale njihove prednosti.
Bibliografija: 20 jed.
Summary ; Sažetak.
Tekst usporedno na engl. i hrv. jeziku.
Keywords: Kartografske projekcije -- Poliazimutne projekcije -- Optimalne projekcije -- Numerička optimizacija